The role of cardiovascular health and vascular events in the relationship between excessive daytime sleepiness and dementia risk - Cavaillès, Clémence; Letellier, Noémie; Berr, Claudine; Samieri, Cecilia; Empana, Jean‐Philippe; Tzourio, Christophe; Dartigues, Jean‐François; Benmarhnia, Tarik; Dauvilliers, Yves; Jaussent, Isabelle (Journal of sleep research, 2024)
Many studies suggest a relationship between excessive daytime sleepiness (EDS) and dementia incidence, but the underlying mechanisms remain uncertain. The study aimed to investigate the role of cardiovascular burden in the relationship between EDS and dementia incidence over a 12‐year follow‐up in community‐dwelling older adults. We performed analyses on 6171 subjects (aged ≥65 years) free of dementia and vascular disease at baseline. Participants self‐reported EDS at baseline and an expert committee validated both prevalent and incident dementia. We defined cardiovascular burden by a low Cardiovascular Health score, constructed using the American Heart Association metrics, and incident vascular events. To explore the potential role of the cardiovascular burden in the relationship between EDS and dementia, we conducted mediation analyses with inverse odds ratio‐weighted estimation, using multivariable‐adjusted proportional hazard Cox and logistic regression models. Subjects with EDS had a higher risk of all‐cause dementia (hazard ratio [HR] 1.39, 95% confidence interval [CI] 1.13–1.69) and dementia with vascular component (DVC) (HR 2.14, 95% CI 1.30–3.51), but not Alzheimer's disease (HR 1.18, 95% CI 0.93–1.51). Cardiovascular burden explained 5% (95% CI 4.1–5.2) and 11% (95% CI 9.7–11.3) of the relationship between EDS and all‐cause dementia and DVC, respectively. These findings confirm that EDS may be implicated in the development of dementia and indicate a weaker than expected role of cardiovascular burden in the relationship between EDS and DVC.